1958
DOI: 10.1002/jlac.19586180128
|View full text |Cite
|
Sign up to set email alerts
|

Darstellung definiert deuterierter Kohlenwasserstoffe

Abstract: Durch Addition von Dialkylaluminiumhydrid bzw. -deuterid an Hexin-( 1) und Hexin-(3) und Hydrolyse bzw. Deuterolyse der entstehenden aluminiumorganischen Verbindungen wurden an bestimmten C-Atomen durch Deuterium substituierte C6-Kohlenwasserstoffe hergestellt.Vor einiger Zeit haben wir 2) iiber die stereospezifische Hydrierung von Acetylenen zu reinen cis-Olefinen berichtet. Die cis-Hydrierung konnte durch Addition eines Dialkylaluminiumhydrids, z. B. des sehr leicht zuganglichen Diisobutylaluminiumhydrids, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1960
1960
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Diethylaluminum deuteride was prepared by reaction of lithium deuteride (Merck Sharp and Dohme, 98% d) with diethylaluminum chloride using a modification of the literature procedure. 65 Lithium deuteride (0.98 g, 0.109 mol) was placed in a flame-dried, twonecked flask equipped with a Teflon stirring bar and a reflux con- Ether (15-20 ml) was added. Diethylaluminum chloride (Texas Alkyls, 13.8 g, 0.115 mol) was weighed into a stoppered 40-ml centrifuge tube and diluted with ether to a total volume of ~30 ml.…”
Section: Methodsmentioning
confidence: 99%
“…Diethylaluminum deuteride was prepared by reaction of lithium deuteride (Merck Sharp and Dohme, 98% d) with diethylaluminum chloride using a modification of the literature procedure. 65 Lithium deuteride (0.98 g, 0.109 mol) was placed in a flame-dried, twonecked flask equipped with a Teflon stirring bar and a reflux con- Ether (15-20 ml) was added. Diethylaluminum chloride (Texas Alkyls, 13.8 g, 0.115 mol) was weighed into a stoppered 40-ml centrifuge tube and diluted with ether to a total volume of ~30 ml.…”
Section: Methodsmentioning
confidence: 99%
“…Given the knowledge about the inertness of ketones that need a reactive vinylating reagent to counterbalance their reduced reactivity, we decided to prepare the organoaluminum compound for the asymmetric addition to ketones because of their high reactivity and the greater lewis acidity of the aluminum center. In a pioneering study, Wilke and Müller demonstrated that dialkylaluminum hydrides add to alkynes via hydroalumination to form vinylaluminum reagents which had been used recently by Hoveyda et al in asymmetric allylic vinylation reactions . By using the same protocol, we prepared the vinylaluminum reagents and successfully applied asymmetric vinyl addition to ketones catalyzed by in situ prepared Ti(O i Pr) 4 complexes of ( S )-BINOL to afford diversified tertiary allylic alcohols in excellent enantioselectivities of up to 98% ee.…”
mentioning
confidence: 98%
“…The addition of diethylaluminum deuteride to 1-alkenes is almost surely a four-center reaction. 32 If the diethylaluminum hydroxide could be reduced with deu-…”
mentioning
confidence: 99%